Distress and Factors for Maintaining Good Mental Health among General Practitioners during the SARS-COV-2 Pandemic - Hoffmann, Kathryn; Stummer, Florian O; Poel, Esther van; Willems, Sara; Wojczewski, Silvia (Archives of Clinical and Biomedical Research, 2025)
Background: The COVID-19 pandemic has had a significant negative impact on the physical and mental health of healthcare workers worldwide. The aim of the paper is to measure the frequency of distress and wellbeing among general practitioners (GPs) in Austria during the pandemic and to identify key levers that could mitigate the risks of distress. Methods: Data were collected as part of the international PRICOV-19 study. In Austria, 500 GPs were randomly selected for participation in a survey between December 2020 and July 2021. For analysis, all dependent and independent variables were described using descriptive statistical methods. Subgroup analyses were conducted using cross-tables and Fisher’s exact tests. A binary logistic regression model was also applied. Open text question was analysed via content analysis. Results: In total, 130 GPs completed the relevant questions for this analysis of the online survey. More than 40% of GPs felt burned out or stated that their work schedules did not leave enough time for personal/ family life. Half of the GPs were found to be in distress, with 14.3% in (very) strong distress. More than 40% of the respondents thought that government support was insufficient for the proper functioning of their practice. Working in rural areas was a protective factor against distress, as were sport and exercise, particularly outdoor activity. Connecting with family and friends and adjustments to the work environment to reduce workload were shown to be important. Discussion: Our results show that GPs in Austria suffered from distress during the first two years of the pandemic. To protect GPs as our firstline healthcare workers in pandemic or high-stress situations, several factors are required for a functioning healthcare system: support of GPs regarding work-life balance, support in terms of collaboration between colleagues and the team and easy access to green outdoor spaces for sports and exercise. By identifying key factors that promote good mental health among GPs, healthcare organizations and policymakers can take targeted action to alleviate the negative impact of stress and burnout on this critical sector of the healthcare workforce.